2013
DOI: 10.18034/ei.v1i2.210
|View full text |Cite
|
Sign up to set email alerts
|

Soil Drainage and Nutrient Management to Improve Productivity of Waterlogged Vertisols for Small-scale Farmers

Abstract: Vertisols cover large part of the high rainfall areas of Ethiopia. However, the potential of these soils is not well exploited because of heavy water logging during the main rain season. A study was conducted to investigate the interactive effects of soil drainage and fertilizer application on the productivity of Vertisols. Factorial combinations of four planting beds (Broadbed and furrow (BBF) with 100 cm bed size, broadbed and furrow with 80 cm bed size, ridge and furrow (RF) with 30 cm bed size, and flatbed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 9 publications
0
2
1
Order By: Relevance
“…e two-year average surface runoff was significantly highest (292.32 mm) in BBF120 and the lowest (255.30 mm) from BBF40. e research finding is in contrast with Mekonen et al [12] who showed the ridge and furrow system drained excess water out of the field due to a large number of furrows constructed on the land that can naturally drain water with a bit provision of furrows. Although the artificial drainage density was relatively higher in BBF40, increased volume of runoff was shown from BBF120.…”
Section: E Effect Of Soil Drainage Methods On Surface Runoffcontrasting
confidence: 68%
See 2 more Smart Citations
“…e two-year average surface runoff was significantly highest (292.32 mm) in BBF120 and the lowest (255.30 mm) from BBF40. e research finding is in contrast with Mekonen et al [12] who showed the ridge and furrow system drained excess water out of the field due to a large number of furrows constructed on the land that can naturally drain water with a bit provision of furrows. Although the artificial drainage density was relatively higher in BBF40, increased volume of runoff was shown from BBF120.…”
Section: E Effect Of Soil Drainage Methods On Surface Runoffcontrasting
confidence: 68%
“…Traditionally, surface roughness is created through the tillage/ridge and furrow system which forms microdepressions in which excess water is stored [23][24][25]. Unlike the case of Mekonen et al [12], these large numbers of microdepressions created by the RF method coupled with a flat slope allow water to be stored along the channel instead of draining out. On the contrary, BBF with a large bed size and a small number of furrows could significantly enable the runoff to be drained from relatively large catchment to furrows widely spaced, and it gets the energy to flow out of the plot through powerful concentration on the channels.…”
Section: E Effect Of Soil Drainage Methods On Surface Runoffmentioning
confidence: 99%
See 1 more Smart Citation